Correction: Iminosugars as glycosyltransferase inhibitors. Issue 25 (18th June 2021) - Conforti, Irene; Marra, Alberto
Abstract : Correction for 'Iminosugars as glycosyltransferase inhibitors' by Irene Conforti, et al., Org. Biomol. Chem., 2021, DOI: ; 10.1039/D1OB00382H .